Peranan Komunikasi Pariwisata PT. Lovely Holidays Medan Dalam Mempromosikan Objek Wisata Daerah Sumatera Utara - Lisan Hot Pandiangan (Jurnal Ilmiah Akomodasi Agung, 2019)
The research, entitled the role of Tourism Communication PT Lovely Holidays Field in promoting Regional Tourism object North Sumatra. Which aims to menganalisisis the tourism communication PT Lovely Holidays Field in promoting regional tourism object North Sumatra, analyze the factors of tourism communications owned PT Lovely Holidays Field, and analyze how promotion of regional tourist attractions of North Sumatra. Research methods using qualitative approach. Informant research taken based on the purposive sample (sample aims). Sample criteria must be active using communications tourism in promoting the attractions of North Sumatra. The selected samples there are 22 people. Data collection through interviews to obtain information from informants, research documents from observation. From the research found that tourists generally satisfied and not feel cheated by the promotional material communicated communicators (PT Lovely Holidays). According to all informants, PT Lovely Holidays strives to present information in a clear and not ambiguous. These maintain the trust customers over tour packages offered.